Minutes of the CCAFS 8th Independent Steering Committee Meeting, 13 & 14 October 2020 - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
In October 2020 the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) held its 8th virtual Independent Steering Committee meeting.